P342 REAL–WORLD ANALYSIS ON THE ECONOMIC VALUE OF REACHING LIPID TARGET IN ITALY. (18th May 2022) - Degli Esposti, L; Borghi, C; Galvani, M; Giacomini, E; Manotti, P; Marra, A; Passaro, A; Perrone, V; Pieraccini, F; Sangiorgi, D; Navazio, A
Abstract: The study aimed to evaluate the healthcare direct costs for Italian National Health System of patients treated with lipid–lowering drugs that do not achieve the low–density lipoprotein (LDL)–cholesterol target compared to those reaching their targets, and to analyze costs according to the distance from LDL target by using real–world data. An observational analysis was performed on administrative and laboratory data from selected Italian Healthcare Departments. Patients were included if they presented at least one laboratory LDL test between 2012 and 2019 and if they were prescribed lipid–lowering drugs during 6 months prior the last LDL detection (index date). Mean annual direct costs were evaluated in the 12 months before index date in terms of all drugs prescribed, all–cause hospitalizations and all outpatient services. Distance to LDL target was calculated as difference between the index LDL level and LDL target. Total mean annual healthcare direct cost for patients that did not reach LDL target was higher compared to total cost of patients achieving LDL target (€3, 678 vs €2, 906). Costs were mainly driven by hospitalization (€1, 330) followed by drugs expenditure (€1, 012) and outpatient services (€563). Mean total annual healthcare costs increased with the distance from LDL target, specifically from €3, 004 for patients with 10% distance from LDL target up to €4, 823 for those 50% or more distance from LDL target. This trend was particularly evident for the cost item related to hospitalization, that went from €1, 486 to €2, 819 moving from 10% to ≥ 50 distance from LDL target. Results from this real–world study highlighted the higher economic burden for patients that do not reach the therapeutic LDL target, that tend to rise along with increasing distance from the LDL target. Overall, our findings could suggest that reducing the distance from LDL target could have a positive impact also on the economic outcomes for these patients.